Implementing the Angoff method of standard setting using postgraduate students: Practical and affordable in resourcelimited settings - A Mubuuke; C Mwesigwa; S Kiguli (South African Medical Association, 2017)
Background. Cut scores for students’ assessments have always been arbitrarily determined in many institutions. Some institutions have adopted reliable methods of determining cut scores, such as the Angoff method. However, use of this method requires many experts, making it difficult to implement in resource-limited settings. The possibility of involving postgraduate students in implementing the Angoff method of setting cut scores could be the solution to this problem.Objectives. To explore the knowledge and practices of faculty regarding standard setting and the feasibility of using postgraduate students when implementing the Angoff method.Methods. This was an exploratory operations research study in which data were collected during focus group discussions. Students were trained to use the Angoff method, i.e. a previous examination, in which the pass mark was 50%, was used to evaluate the method.Results. Initial findings showed that faculty in the consortia of schools did not know what standard setting and the Angoff method entailed and had never used this approach. The postgraduate students involved in implementing the Angoff method of setting cut scores were excited and interested in engaging in the exercise; the pass mark they arrived at was 61.21%.Conclusion. The study demonstrated that it is feasible to use the Angoff method of determining pass marks, even in resource-limited settings. This can be made possible by involving postgraduate students in the absence of enough faculty experts.